SOFTWARE FOR CYBER PROTECTION OF THE STATE AGAINST CYBER ATTACKS - Blavatska, Nataliya; Brailovskyi, Mykola; Kozura, Valeriy; Khoroshko, Volodymyr (Ukrainian Information Security Research Journal, 2023)
The protection of the state’s critical infrastructure objects from cyber-attacks, especially in the conditions of hostilities, requires state bodies to take effective cyber protection measures. The basis of such measures is the development of state targeted cyber protection programs. When forming requirements for modern cyber protection systems, a number of tasks must be solved, the main ones of which include determining the characteristics of the impact of cyber-attacks on cyber protection systems, quantitative indicators of the effectiveness of cyber threat protection systems, and the optimal allocation of limited resources for the implementation of effective cyber protection. Based on the modification of known methods of target assessment of alternatives, the work develops a method of supporting decision-making in the formation of complex target programs of cyber protection of critical infrastructure objects in the conditions of the enemy’s implementation of cyber-attacks, various threats and risks. The main idea of the proposed approach to the analysis of the impact of cyber-attacks when implementing a cyber-defense program is that the events that contribute to cyber-attacks are considered as an integral part of the cyber-defense system, that is, as an influence of the external environment. Therefore, such models of cyberattacks are included in the hierarchy of goals of the cyber defense program, their connections with other systems and goals of state target programs are established. The effectiveness of such programs is evaluated in the presence of cyber-attacks, considering their probable characteristics. Proposed models of cyber-attacks and risks. A model of a cyberattack is a program project, which is included in the hierarchy of goals of a comprehensive program, which is described by the degree and probability of implementation. The risk model is built from two components: a risk factor, which is described by a random process, and some fictitious target – a risk indicator.